Islamic Values in the World Today – Indonesia and the Islamic World - Hans-Christian Günther (Sunan Kalijaga: International Journal of Islamic Civilization, 2021)
The present paper is dedicated to answer the question on how Islamic values contribute to today’s multicultural societies. In this context, Indonesia is a good example with its basic tenets of Indonesian state ideology. I argue that this state ideology is coined by Islamic values, but the Indonesian state does not fully live up to these values, because there is no proper input of Islam. Learning from the Indonesian model, I am sure that Islam is not only fully compatible with democracy and a multicultural society, it is also the religion which, if applied in its true sense, can best deal with multicultural and multi religious societies as was stated in the Bhineka Tunggal Ika (Unity in Diversity) principle.